Recent Advances in Nanostructured Biomimetic Dry Adhesives - Pattantyus-Abraham, Andras; Krahn, Jeffrey; Menon, Carlo (Frontiers in Bioengineering and Biotechnology, 2013)
The relatively large size of the gecko and its ability to climb a multitude of structures with ease has often been cited as the inspiration upon which the field of dry adhesives is based. Since 2010, there have been many advances in the field of dry adhesives with much of the new research focusing on developing nanoscale and hierarchical features in a concentrated effort to develop synthetic gecko-like dry adhesives which are strong, durable, and self-cleaning. A brief overview of the geckos and the hairs which it uses to adhere to many different surfaces is provided before delving into the current methods and materials used to fabricate synthetic gecko hairs. A summary of the recently published literature on bio-inspired, nanostructured dry adhesives is presented with an emphasis being placed on fabrication techniques.